Pengaruh Media Pembelajaran Articulate Storyline Terhadap Hasil Belajar Peserta Didik pada Pembelajaran Matematika - Putri Selviana; Eliya Rochmah; Sati Sati (CV. ULIL ALBAB CORP, 2024)
This study aims to 1) find out how the use of Articulate Storyline media in grade IV of SD Negeri 2 Kalibuntu, 2) find out how the learning outcomes of students in Mathematics learning in grade IV of SD Negeri 2 Kalibuntu, 3) find out how the use of articulate storyline media affects the learning outcomes of students in Mathematics learning at SD Negeri 2 Kalibuntu. The research design used in this study uses a quantitative method using a pre-experimental design approach in the form of one group design pre-test-post testt. The subjects of this study consist of 15 students. The data collected used teacher performance observation sheets, student observation sheets and test questions before and after the use of learning media. The results of the study were based on 1) observations made on teacher performance, teacher performance before using Articulate Storyline learning media obtained a total score of 14 (66%) with sufficient criteria. Meanwhile, the teacher's performance after using the Articulate Storyline learning media obtained a total score of 19 (90%) with very good criteria. 2) The test results showed a significant increase in test scores before and after using the media, with an average score of 56.33 for pretest learning outcomes and 79 for posttest learning outcomes. 3) Based on the results of the Paired Sample T test, it is known that the value of Sig. (2-tailed) is 0.000 < 0.05, then Ho is rejected and Ha is accepted.